Experimental Investigation of Energy Absorption Characteristics of Square Thin-Walled Aluminum Tubes under Folding and Splitting Deformation Modes - Mahmoodnezhad, Motahare (Mechanical Technology and Engineering Insights, 2024)
Thin-walled metal structures have been used extensively in energy absorption systems in various fields such as transport, aerospace, and protection engineering because of their excellent properties, particularly their high strength-to-weight ratios and high energy absorption performance. This paper experimentally evaluates the energy absorption behavior of square thin-walled aluminum tubes subjected to two different deformation behaviors: folding and splitting. The specimens used in all experiments were made of the same type of aluminum material. They had the same geometrical parameters, such as wall thickness, tube length, cross-sectional dimensions, and volume. The dynamic compressive tests were carried out on the specimen samples through the folding deformation method using the drop-hammer machine. The results of the experiment indicated that folding deformation has a better performance in terms of energy absorption capacity with a  Specific Absorbed Energy (SAE) value of 15,601.6 J/kg, which is 14.1% higher than that achieved through splitting. In addition, the average crushing force observed during the folding mode tests is about 45% higher compared to that recorded for the splitting deformation mode. On the other hand, the splitting mode yielded a considerably lower maximum force value but had a longer crushing displacement, making it more stable in its force-displacement response. The observations during deformation showed consistent diamond-shaped progressive folding deformation for folding samples, but curling without periodic folds in splitting samples. From the results obtained, it can be deduced that folding is better suited where maximum energy absorption capacity is the key objective.